URGENSITAS PUBLIC RELATION DALAM MEMPERJUANGKAN AKSI FEMINISME MELALUI MEDIA JURNALISTIK ONLINE DI KOTA MEDAN - Taufiq Nurrahmad; M. Yoserizal Saragih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Public relations is a group of people who pay attention to the same things, have the same goals, and the same interests. Public is a collection consisting of a small number and can also be a large number. Public relations is always related to communication. Communication is an important aspect of life. This study aims to educate that the problem of femenism is a big and complicated problem. Public relations and journalists must take part in this movement where public relations as spokespersons and journalists who are a forum for liaison between public relations and the community both through mass media, online media, and most interestingly through social media. This research was conducted through observation to find out the direct situation of how the people of Medan responded to public relations efforts in handling feminism actions and cases in the city of Medan. The process of data collection and information collection is carried out in the form of primary and secondary data collection. Primary data were obtained from field observations in the form of direct visits to the research location by conducting direct interviews with resource persons, namely Mr. Heriyono and Mrs. Nuri and several UINSU students. Secondary data is obtained from: articles, literature, theses, scientific journals, and scientific reports related to public relations and feminist action through online media. The data obtained from the results of this study were collected, then processed and analyzed using descriptive qualitative research methods